Granada Virus: a Natural Phlebovirus Reassortant of the Sandfly Fever Naples Serocomplex with Low Seroprevalence in Humans - Collao, Ximena (The American Society of Tropical Medicine and Hygiene, 2010)
A new member of the phlebovirus genus, tentatively named Granada virus, was detected in sandflies collected in Spain. By showing the presence of specific neutralizing antibodies in human serum collected in Granada, we show that Granada virus infects humans. The analysis of the complete genome of Granada virus revealed that this agent is likely to be a natural reassortant of the recently described Massilia virus (donor of the long and short segments) with a yet unidentified phlebovirus (donor of the medium segment).